Genome-wide genetic investigation of serological measures of common infections - Rubicz, R.; Yolken, R.; Drigalenko, E.; Carless, M.; Dyer, T.; Kent, J.; Curran, J.; Johnson, M.; Cole, S.; Fowler, S.; Arya, R.; Puppala, S.; et al. (2015)
Populations and individuals differ in susceptibility to infections because of a number of factors, including host genetic variation. We previously demonstrated that differences in antibody titer, which reflect infection history, are significantly heritable. Here we attempt to identify the genetic factors influencing variation in these serological phenotypes. Blood samples from >1300 Mexican Americans were quantified for IgG antibody level against 12 common infections, selected on the basis of their reported role in cardiovascular disease risk: Chlamydia pneumoniae; Helicobacter pylori; Toxoplasma gondii; cytomegalovirus; herpes simplex I virus; herpes simplex II virus; human herpesvirus 6 (HHV6); human herpesvirus 8 (HHV8); varicella zoster virus; hepatitis A virus (HAV); influenza A virus; and influenza B virus. Pathogen-specific quantitative antibody levels were analyzed, as were three measures of pathogen burden. Genome-wide linkage and joint linkage and association analyses were performed using ~1 million SNPs. Significant linkage (lod scores >3.0) was obtained for HHV6 (on chromosome 7), HHV8 (on chromosome 6), and HAV (on chromosome 13). SNP rs4812712 on chromosome 20 was significantly associated with C. pneumoniae (P=5.3 × 10 -8). However, no genome-wide significant loci were obtained for the other investigated antibodies. We conclude that it is possible to localize host genetic factors influencing some of these antibody traits, but that further larger-scale investigations will be required to elucidate the genetic mechanisms contributing to variation in antibody levels.